CrabCare: Innovative Chitosan Biopolymer-Based Ointment from Crab Shell Waste by Utiling - Maulin Navla; Aprilia Rachma Ade; Nainggolan Rustani; Pardi H.; Coklin Barit (BIO Web of Conferences)
Wounds are a common problem that requires effective care to prevent infection and accelerate the healing process. The use of conventional antiseptics is often unsatisfactory due to the long time required. Therefore, the innovation of using chitosan from crab shell waste as a base material for ointment becomes the focus of this research. This study aims to develop a chitosan-based ointment that can accelerate the wound healing process more efficiently. The research results show that the ointment developed from crab shells through the deproteinization process can significantly accelerate wound healing. Chitosan extracted from crab shells has unique properties such as bioactivity, biodegradability, and biocompatibility, which are effective in inhibiting bacterial and pathogen growth, as well as stimulating granulation tissue formation. Thus, the CrabCare ointment made from crab shell chitosan offers a promising alternative as a therapeutic agent for more effective and environmentally friendly wound care. In conclusion, the development of CrabCare provides new opportunities in wound therapy through innovative and sustainable means.